Empowering women : issues, challenges and strategies - Das, Mandakini, 1928-; Daspattanayak, Pritirekha, 1962- (New Delhi : Dominant Publishers and Distributors, 2009)
With special reference to Orissa.
Contributed articles.
Includes bibliographical references.
Keywords: Women in development -- India; Women -- Government policy -- India; Rural women -- Government policy -- India -- Orissa; Tribes -- Government policy -- India -- Orissa